The development of cross-border economic relationships between firms in border regions - Henk Van Houtum (European Regional Science Association (ERSA), 1998)
Central question of this paper is what effects a state border has on the development of cross-border economic relationships in border regions. First the geographical spread of these relationships is analysed. Next a theoretical model is proposed to explain the pattern and the decision-process of bilateral international economic relationships. The model is mainly based on four theories: 1. the transaction costs approach on cross border economic relations under the condition of uncertainty. 2. The 'psychic distance' approach, which considers internationalization as an incremental learning process. The speed of the internationalization of a firm is determined by the experiential knowledge about the foreign country. 3. The network-approach, which considers (international) markets as networks. Firms are linked in patterns of cooperation and affiliation. Cooperation and not efficiency of transactions determine the behaviour of firms. 4. The socio-psychological approach of relations and social identity, which stresses the role of cognitive and affective aspects of cross-border relationships. These theories have lead to the model of INTERnational Formation of Autonomous Cooperation between Entrepreneurs (INTERFACE). The INTERFACE model distinguishes between different phases of relationship-building, namely contact, attraction (the choice for the partner), interaction (the negotiation about the conditions), transaction (the realization of the agreement/contract) and relationship. This relationship-development model is used to describe the process of the development of cross-border economic relationships and to explain the number and success of cross-border economic relationships. The model is empirically tested for a large sample of firms in two Dutch-Belgian border regions. The study is part of a dissertation on the development of cross-border economic relationships. The findings of the model suggests that the action-space of the firms, in terms of informal embeddedness and economic relationships, is spatially limited by the presence of the border. The factors of similarity and trust between the partners are found to be the most important determinants of success of cross-border economic relationships. The dimensions of expectations on the discrepancy in business conventions, the expectations on the success of economic relations in the neighbouring country and the strictness of the financial-economic terms of the relationship play a major role in determining the number of cross-border economic relationships. This is defined as the 'mental distance' effect of borders.
Keywords: 330